Health care's climate footprint: the health sector contribution and opportunities for action. (30th September 2020) - Karliner, J; Slotterback, S; Boyd, R; Ashby, B; Steele, K; Wang, J
Abstract: While vastly differing in scale, each nation's health sector directly and indirectly releases greenhouse gases (GHG) through energy consumption, transport, and product manufacture, use, and disposal. Until recently, however, the health sector has not been measured as a coherent segment of the world's climate footprint. A 2019 report by Health Care Without Harm, in collaboration with Arup, provides the most comprehensive global analysis of health care's contribution to climate change to date, based on full global coverage of spending data together with detailed information from 43 countries. It identifies key sources of health care emissions while allowing for comparison between nations and among many regions of the world. Among the report's key findings are that health care's climate footprint is equivalent to 4.4% of global net emissions; that the top three health care emitters-the United States, China, and the European Union-comprise more than half of the global footprint; and that 71% of emissions are derived from the health care supply chain. The findings inform a series of international, national, and subnational policy recommendations for health care climate action, and it identifies opportunities for further research and methodological development to support the health sector in its efforts to understand and address its climate footprint. Additional findings from 2020 will also be presented. Ultimately, these estimates of health care's climate footprint provide the baseline information needed to devise pathways and track progress toward health care de-carbonization across the sector.